From Logical Structure to Critical Reasoning: Philosophical Perspectives on Venn Diagrams as Epistemological Tools - Ahmad, Andi Kamal; Nurcholish Aziz; Marjuni; Afifuddin Harisah; Muhammad Amin (Global Action and Education for Society, 2026)
This paper addresses the research gap where the Venn Diagram is narrowly viewed as a technical tool in set theory, overlooking its profound philosophical role in logic. By employing a qualitative literature review that synthesizes classical philosophical texts on logic with contemporary mathematical analysis, the study aims to recontextualize the Venn Diagram as a critical epistemological instrument for valid reasoning. The methodology focuses on integrating foundational principles of philosophy with the diagram's procedural mechanics. The analysis reveals that the systematic notation of the Venn Diagram (shading for null sets and 'x' for existential import) provides a formal, visual procedure for testing the validity of syllogistic arguments. This process effectively transforms abstract logical structures into a tangible